The Implementation of English Teachers’ Authentic Assessment in Junior High School During Online Learning - Putri, Ni Wayan Astri Monika; Artini, Luh Putu Putu; Sulistia Dewi, Ni Luh Putu Eka; Paramartha, A.A. Gede Yudha; Wahyuni, Luh Gede Eka (Journal of Education Reseach and Evaluation, 2021)
Authentic assessment is assessment to define students’ reflection of their learning, achievement, motivation, and attitudes during the learning instruction. Authentic assessment will cover the educational content standard as requested in educational process standard. Implementing authentic assessment reflects real-world situation and allow students to solve problem with possible solutions. This research aimed at investigating the English teachers’ authentic assessment implementation during online learning. This research was descriptive qualitative research. The research subject was three English teacher. The research object was the English teachers’ implementation of authentic assessment. In collecting the data, this research used document study and interview. The data were analyzed through three steps; data reduction, data classification and analysis, and conclusion drawing or data verification. After analyzing the obtained data, the English teachers used five types of authentic assessment namely teacher’s observation, performance, portfolio, project, and peer-assessment. Besides, in the learning instruction, the English teachers did not implement all of the types of authentic assessment in all learning material. The English teachers did not implement all the types of authentic assessment as their lesson plans considering some problems faced by the English teachers. Limited time allotment, many students in one class, and also students’ learning materials become the teachers’ problems. Thus, the implementation of authentic assessment needs to be reviewed in order to help the English teachers in implementing the authentic assessment.